2018
DOI: 10.3389/fphys.2018.01265
|View full text |Cite
|
Sign up to set email alerts
|

Early Functional and Morphological Muscle Adaptations During Short-Term Inertial-Squat Training

Abstract: Purpose: To assess early changes in muscle function and hypertrophy, measured as increases in muscle cross-sectional areas (CSAs) and total volume, over a 4 weeks inertial resistance training (RT) program.Methods: Ten young RT-naive volunteers (age 23.4 ± 4.1 years) underwent 10 training sessions (2–3 per week) consisting of five sets of 10 flywheel squats (moment of inertia 900 kg⋅cm2). Magnetic resonance imaging (MRI) scans of both thighs were performed before (PRE), and after 2 (IN) and 4 (POST) weeks of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 44 publications
2
31
0
1
Order By: Relevance
“…MV results are shown as the average of right and left thighs. The intra-investigator coefficient of variation for muscle segmentation was 1.1% ± 0.4% for the muscles assessed; similar to previous estimations of error for this method [22,23].…”
Section: Methodssupporting
confidence: 87%
“…MV results are shown as the average of right and left thighs. The intra-investigator coefficient of variation for muscle segmentation was 1.1% ± 0.4% for the muscles assessed; similar to previous estimations of error for this method [22,23].…”
Section: Methodssupporting
confidence: 87%
“…A recent meta-analysis about the effects of flywheel training on Strength-Related Variables show that the majority of these studies were carried out on periods of training between 5 and 10 weeks ( Petré et al, 2018 ). However, more concretely, another recent study demonstrated that 4 weeks could be enough time to show muscle adaptation in flywheel resistance training ( Illera-Domínguez et al, 2018 ). Further, in horizontal inertial flywheel training, which has more similarity to our study ( de Hoyo et al, 2015 ; Gonzalo-Skok et al, 2016 ), differences in power and functional performance in 6- and 8-week period training were found.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, volume for these muscles in MJ exercises must be accounted for at a lower percentage on a set basis. However, the validity of MRI has been called in question as a measure for predicting long-term muscular adaptations [48], raising some skepticism as to the practical implications of its correlation with EMG.…”
Section: Acute Studiesmentioning
confidence: 99%